Duchenne and Becker muscular dystrophy in adolescents: current perspectives - Andrews JG; Wahl RA (Dove Medical Press, 2018)
Jennifer G Andrews, Richard A Wahl Department of Pediatrics, University of Arizona, Tucson, AZ, USA Abstract: Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are life-limiting and progressive neuromuscular conditions with significant comorbidities, many of which manifest during adolescence. BMD is a milder presentation of the condition and much less prevalent than DMD, making it less represented in the literature, or more severely affected individuals with BMD may be subsumed into the DMD population using clinical cutoffs. Numerous consensus documents have been published on the clinical management of DMD, the most recent of which was released in 2010. The advent of these clinical management consensus papers, particularly respiratory care, has significantly increased the life span for these individuals, and the adolescent years are now a point of transition into adult lives, rather than a period of end of life. This review outlines the literature on DMD and BMD during adolescence, focusing on clinical presentation during adolescence, impact of living with a chronic illness on adolescents, and the effect that adolescents have on their chronic illness. In addition, we describe the role that palliative-care specialists could have in improving outcomes for these individuals. The increasing proportion of individuals with DMD and BMD living into adulthood underscores the need for more research into interventions and intracacies of adolescence that can improve the social aspects of their lives. Keywords: adolescent health, review, Duchenne muscular dystrophy, Becker muscular dystrophy, dystrophinopathy, palliative care